THE DEVELOPMENT OF OGOH-OGOH MAKING WITH KINETIC ART’S TECHNOLOGY IN DENPASAR CITY - I Gusti Nengah Sura Ardana; I Ketut Sudita (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
Ogoh-Ogoh is a three-dimensional kind of sculpture made at the time of pengrupukan in Bali, which is very closely related to the celebration of the Nyepi day of the Hindus in Bali as the new year, which comes once a year. In welcoming this celebration, there is something called tawur sange or the pecaruan ceremony, which means purifying the earth, carried out the day before the Nyepi celebration. The purpose of this celebration is to neutralize the forces of power of the negative that often interfere with human life, known as Bhuta Kala. It is what in Somia (neutralize) to be a good force (positive) and become the power of God. During this celebration, ogoh-ogoh are made that resemble the shape of Bhuta Kala or negative power whose shape is made very scary according to the imagination of the artists/young people who make it. The shape and appearance of the ogoh-ogoh today have progressed very rapidly. The development of making ogoh-ogoh today is very rapid and has experienced a very amazing increase, and it is because young people (yuwana) are developing creativity and innovation in making ogoh - ogoh. The innovation made is by incorporating elements of technology, namely Kinetic Art technology, into the manufacture of ogoh-ogoh, so that the ogoh-ogoh seem alive because they move. This research was conducted in Denpasar City with qualitative methods in data collection and has the purpose and benefit of knowing in depth about the development of ogoh-ogoh in the present. Keywords : Development, Ogoh - Ogoh, Kinetik Art